A beacon of knowledge and faith: the new Imam Al-Bukhari Mosque in Samarkand - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
The historic city of Samarkand will soon witness a momentous occasion, the official opening of the Imam Al-Bukhari Mosque, a majestic new centerpiece within the Imam Al-Bukhari Memorial Complex in Khartang Village, a suburb in Samarqand, Uzbekistan. This opening does not only celebrate the remarkable architectural achievement but also revives a centuries-old legacy of scholarship, spirituality, and service to humanity. The new mosque stands near the resting place of Imam Muhammad ibn Isma'il Al-Bukhari (810-870 CE), one of Islam's most revered scholars and the compiler of Sahih al-Bukhari, universally regarded as the most authentic collection of Hadith after the Qur'an. The mosque indeed epitomizes Uzbekistan's effort in honoring a scholar of timeless influence. For centuries, visitors and scholars from around the world have visited his mausoleum in Khartang, a humble site that has now evolved into a global center of knowledge, faith and learning. Following Uzbekistan's independence, the government and international partners launched extensive efforts to restore and expand the Al-Bukhari Memorial Complex, transforming it into a space that reflects both deep reverence for the past and optimism for the future. The Complex which is a new landmark for Central Asia houses various significant buildings, including the newly constructed Imam Al-Bukhari Mosque.